The Collection of Late Antique Textiles from Egypt Acquired in 1893 by the Archaeological Cabinet of the Jagiellonian University in the Context of the Early Interest in “Coptic” Weaving .......... 287 - Głowa, Anna; Sławińska, Joanna (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
Since 1883, when Theodor Graf (1840–1903) exhibited in Vienna a collection of Late Antique textiles from Egypt, a new trend in collecting antiquities was born. In the next decades, thousands of such textiles got to museums and private collections throughout the world. Some treated them as curiosities, others as examples of ancient craft to serve educational purposes, still others valued them as objects that enriched the knowledge of the daily life and culture in the centuries of the transformation of the ancient civilization. One of the oldest collections of this kind in Poland is an assembly of 52 textiles acquired in 1893 by professor Józef Łepkowski (1826–1894) for the Archaeological Cabinet of the Jagiellonian University (currently the Jagiellonian University Museum). The paper presents the Archaeological Cabinet’s collection of textiles on a broader background of the 19th-century interest in this specific kind of objects.